2021
DOI: 10.15585/mmwr.mm7010e4
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Risk for COVID-19–Related Hospitalization, Intensive Care Unit Admission, Invasive Mechanical Ventilation, and Death — United States, March–December 2020

Abstract: On March 8, 2021, this report was posted as an MMWR Early Release on the MMWR website (https://www.cdc.gov/mmwr). Obesity* is a recognized risk factor for severe COVID-19 (1,2), possibly related to chronic inflammation that disrupts immune and thrombogenic responses to pathogens (3) as well as to impaired lung function from excess weight (4). Obesity is a common metabolic disease, affecting 42.4% of U.S. adults (5), and is a risk factor for other chronic diseases, including type 2 diabetes, heart disease, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
320
5
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 372 publications
(378 citation statements)
references
References 9 publications
41
320
5
12
Order By: Relevance
“…In contrast to obesity, the relationship between underweight and COVID-19 is unknown. A recent study showed a J-shaped (non-linear) relationship between BMI and risk for COVID-19 related hospitalization, ICU admission, and death [28]. In our study, subjects with a BMI � 30 kg/m 2 presented higher fatality with an odds ratio of 4.32, compared to subjects of a 23 �BMI < 25 kg/m 2 .…”
Section: Plos Onesupporting
confidence: 53%
“…In contrast to obesity, the relationship between underweight and COVID-19 is unknown. A recent study showed a J-shaped (non-linear) relationship between BMI and risk for COVID-19 related hospitalization, ICU admission, and death [28]. In our study, subjects with a BMI � 30 kg/m 2 presented higher fatality with an odds ratio of 4.32, compared to subjects of a 23 �BMI < 25 kg/m 2 .…”
Section: Plos Onesupporting
confidence: 53%
“…However, contrary to most recent publications [32], Figure 4b shows that higher BMI decreased the likelihood of being labelled as deceased. Higher BMI being associated with better outcomes has also been reported in veterans [33]. This may be attributed to collider bias, as the number of obese people outnumber the non-obese people in our cohort and obese people are also more likely to be hospitalized for COVID.…”
Section: Discussionsupporting
confidence: 61%
“…Other analyses of hospital stay time applying the survival analysis techniques can be found in the literature and Factors potentially associated with hospital stay time, e.g, obesity, which may have a nonlinear impact on COVID-19 severity, the prescription of drugs ACEi and/or ARB. [41][42][43][44][45][46] Due to a lack of related information in our dataset, we are unable to compare with these published results.…”
Section: Discussionmentioning
confidence: 88%